International economic co-operation and the World Bank - Oliver, Robert W. (London : Macmillan, 1975)
On December 14, 1945, the House of Commons voted 314 to 50 to ratify the Agreements negotiated at Bretton Woods, New Hampshire, nearly a year and a half earlier. Lord Keynes had returned from Washington to defend the Fund and the Bank, of which he and Harry White were the principal authors, as well as to justify an American loan to Britain - following President Harry S. Truman's abrupt postwar decision to terminate all land-lease assistance to its wartime allies, an event which induced the Conservative MP Robert Boothby, to declare: This is our economic Munich.
Includes bibliographical references: p. [395]-412. and index
rpm 14/11/2017
Loans
Keywords: World Bank; International economic relations; International finance; Banks and banking, International; Economic assistance; International cooperation